Mirror image serum lipid carrier protein profiles in pup and lactating mother Atlantic grey seals reflect contrasting resource mobilisation challenges - McGill, Suzanne; Burchmore, Richard J. S.; Pomeroy, Patrick P.; Kennedy, Malcolm W. (Frontiers in Marine Science, 2022)
True, phocid seals have the shortest known lactations relative to body mass, during which mass transfer of adipose stores from mother to offspring occurs at an unrivalled rate and extent. The mothers of most species of seal fast until weaning whilst their pups gorge on the most fat-rich milks known. This results in a dramatic reduction in maternal blubber mass while pups may triple their body weights before weaning. Mothers mobilise their blubber fat, transport it via blood to their mammary glands and into milk, whilst pups transfer fat in the opposite direction, from their intestines, via blood, to their blubber. Using proteomic analysis of mother and pup sera from Atlantic grey seals, we find that this mirror image flux of lipids between mothers and pups is reflected in an almost inverse relationship in the proteins in their blood specialised to transport fats, lipids, and fat-soluble vitamins. For instance, apolipoproteins ApoB-48/100, ApoA-II and ApoA-IV, which are structural components of the main lipid carrier complexes such as chylomicrons and HDL particles, occur at much higher levels in pups than mothers. Meanwhile, carriers of fat-soluble vitamins such as retinol- and vitamin D-binding proteins are lower in pups and gradually build towards weaning. In contrast, sex hormone-binding globulin occurs at remarkably high relative concentrations in pups. There are therefore dramatic differences between, and an unrealised complexity in, the balance of proteins involved in the rapid transfer of fats and other lipids from mother to pups in preparing their offspring for their post-weaning fasts on land and eventual survival at sea before they can feed again.